Behavior of silk protein at the air-water interface - Yang, Y; Dicko, C; Bain, C; Gong, Z; Jacobs, R; Shao, Z; Terry, A; Vollrath, F (2012)
The inability to link silk biomacromolecules' activity to their self-assembly and further fiber formation has limited a true implementation of a silk biotechnology. In this paper, we describe the application of video-enhanced drop shape analysis and interfacial shear rheological measurement to characterize the dynamic surface activity and interfacial interactions, as well as molecular structure within the interfacial layer of silk proteins. Quantitative analysis of the dynamic surface tension highlights two major mechanisms: (i) a mixed model at low concentration, and, (ii) a diffusion limited model at higher concentration. Once regenerated silk fibroin (RSF) is adsorbed at the air-water interface, interfacial gel-like structures are formed. The interfacial elastic modulus (G′) of the adsorbed membranes exhibited a non-monotonic concentration dependence with a local maximum value at 1.0 × 10-5 g mL-1, indicating a different surface structure formed in RSF solution. The viscoelastic behavior varies with RSF concentration corresponding to three states of a soft glassy system, i.e. below, above and near the glass transition. A structural model for RSF adsorbed layers at the air-water interface at different bulk concentrations is suggested. © 2012 The Royal Society of Chemistry.